CUTTING-EDGE MATERIALS USED IN CONSTRUCTION OF WIND GENERATORS - Ablyametov Siyar Murat ugli; Toirov Olimjon Zuvurovich; Abduganiev Javokhir Sherzod ugli (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Annotation: Wind power is increasingly vital for sustainable energy, driving the need for advanced materials in wind turbine construction. This article explores the latest innovations in materials that enhance the performance, durability, and efficiency of wind turbines. We provide a historical overview of traditional materials and their evolution into today's advanced composites and alloys, including fiberglass reinforced plastics, carbon fiber composites, high-strength steel, and aluminum alloys, each offering unique benefits such as superior strength and corrosion resistance.